Diffusive non-tumoral pathology of the breast: current state of the problem. Diagnosis and treatment of mastalgia - O.S. Zotov (Publishing House TRILIST, 2021)
In the twentieth century, a whole teaching of mastopathy was formed. However, over time, accumulated data have questioned the existence of mastopathy as a separate nosological form, because the term "fibrocystic disease" while mastalgia is the most common symptom does not correspond to a holistic concept of the disease. This "disease" can be diagnosed in any woman and more or less successfully treated. In the United States, this term was obsolete in 1985. Instead, the term ANDI (Aberrations in the Normal Development and Involution of the breast) was proposed, which correctly corresponds to the pathogenesis. Leading guidelines on management of benign diseases of the breast now use this term. Therefore, treatment is necessary only for a very limited number of patients. Cyclic mastalgia is required therapeutic intervention, which in most cases is classified as a "disorder" according to the ANDI classification. There are the following types of mastalgia that require medical intervention: cyclic, non-cyclic, extramammary. Homogeneous evidence has been obtained in favor of antigonadotropins, dopamine agonists, selective estrogen receptor modulators, gonadotropic releasing hormone agonists among non-surgical methods of treatment of cyclic mastalgia. A number of numerous studies have shown that Vitex agnus castus can reduce pain and discomfort in patients with cyclic mastalgia and its effects can be compared with the effects of bromocriptine and cabergoline. The European Medicines Agency has recognized Vitex agnus castus extract, obtained by extraction with ethanol 60% (Prefemin), as the only extract with the status of "widespread medical use" for the treatment of premenstrual syndrome. Prefemin is well studied, its efficacy and safety, as well as satisfactory long-term tolerability have been proven in European clinical trials evidenced A. Therefore, Prefemin as a preparation with a high dosage of Vitex agnus castus extract can be considered as the drug of choice for premenstrual syndrome.